Survey on Autonomous Beach Cleaning Robot (B-BOT) - Thakur, Mrinalini; VARGHESE, Sunny; Kumar, T. Senthil (International Journal of Psychosocial Rehabilitation, 2020)
Autonomous machines are being used more and more with each passing day. With growing problems around the world artificial intelligence controlled robots have stepped in to make most of the tasks easier and more efficient while reducing manual labour immensely. In recent years, use of robots for helping humans in accomplishing various tasks has accelerated greatly. In this study, a comprehensive survey on the various methods of autonomous robots which are mainly directed towards garbage cleaning. Robots currently in use have cons such as high implementation cost, not user friendly and remote control access only available. Reviews of earlier autonomous robot systems use various algorithms like Backtracking Spiral Algorithm which helps to determine the area of travel and sensors for object detection are being studied. However, with the existence of Internet of Things better algorithms have been discovered which help in the bot motion on surface area. Also, an over view of few object detection and recognition algorithms which help us determine between scrap and other entities.